Marketing Communication Strategy of Dehasen University to Attract Prospective Students in Digital Era - Laini, Mesa; Narti, Sri; Dianthi, Martha Heriniazwi (Social Sciences Journal, 2025)
In today’s increasingly competitive higher education sector, universities must adopt strategic and adaptive marketing communication approaches to attract prospective students. This study analyzes the communication strategy of Dehasen University Bengkulu (UNIVED) by applying Kotler’s Promotion Mix framework, which includes advertising, sales promotion, personal selling, public relations, and direct marketing. The research uses a descriptive qualitative method with data collected through interviews, observation, and documentation from key figures within the university's new student admission committee. Findings show that UNIVED effectively combines traditional and digital media, including AI-based content creation for social media platforms like Instagram and TikTok. Advertising is supported by printed brochures and banners, while sales promotions include scholarships, fee discounts, and referral incentives. Personal selling is conducted via school visits and education fairs, building trust through face-to-face engagement. Public relations efforts are maintained through media exposure and community involvement, enhancing institutional credibility. Direct marketing employs personalized messages via WhatsApp, email, and social networks. From 2020 to 2024, student enrollment steadily increased, indicating the strategy’s effectiveness. The study concludes that integrated, technology-based, and student-focused communication enhances institutional visibility and appeal. UNIVED is encouraged to strengthen two-way digital communication to remain relevant and competitive in the digital era.